Aplicabilidade da teoria educacional de Émile Durkheim no ensino superior do Brasil contemporâneo - Rocha, Ronaldo Inácio (2016)
The scope of this dissertation is to make a theoretical and conceptual study of the work of Émile Durkheim with regard to the educational question and to verify to what extent his writings contribute to the understanding of the higher education of contemporary Brazil, which is subject to the laws and regulations Of public power. The method and object of Durkheim's Sociology are presented, proposing comparisons between the classical or traditional educational sociological perspective of the thinker and the humanist, which is present in contemporary Brazil. It focuses on education-related morality in Durkheim's work as an act that serves the interests of society as formal structures of reason, not religion. Individuals are socialized by becoming aware of the need for voluntary adherence to socially imposed rules that are determinant of the student's duties and which resemble the rules that prescribe adult conduct. Moral education is embedded throughout the student's school life. International agreements, globalization of education policies and the transformation of education into an investment source, which characterized the last decades of the twentieth century and the beginning of the twenty-first century, were also analyzed, when human capital theory was recovered and applied in the educational sphere, associating Higher education to the achievement of skills that enable social ascension. In this perspective, what matters is the insertion in the labor market, while an imposition of the current system on the formation of human capital, coupled with the students' suitability to the neoliberal precepts, in which competence and the attainment of skills are more relevant than the historical-scientific knowledge capable of transforming, through the process of schooling, the way of thinking reality.